Risk Factors for HIV and AIDS at the Harapan Health Center, East Sentani District, Jayapura Regency in 2023-2024: HIV/AIDS - Almung, Winsi; Hasmi, Hasmi; Pariaribo, Konstantina M.; Bouway, Dolfinus Y.; Tuturop, Katarina L.; Nurdin, Muhammad Akbar (Formosa Journal of Science and Technology, 2025)
This study aims to determine the risk factors for HIV and AIDS incidence at the Harapan Health Center. Observational analytical research with a case control approach. The sampling technique uses purposive sampling. The population, namely all those who are tested for HIV and AIDS at the 2023-2024 Harapan Health Center, is 965 people with a sample size of 64 additional control cases. The results of bivariate analysis showed a significant relationship between the number of sexual partners (p-v=0.001, OR=21,211, 2,565-175,404) and STI history (p-v=0.000, OR=8,273, 2,622-26,100) with the incidence of HIV and AIDS. Meanwhile, it did not show a significant relationship between age variables (p-v=0.708, OR=1.970, 0.390 - 8.220), gender (p-v=0.439, OR=1.711, 0.616 - 4.769), educational history (p-v=1.000, OR=0.802, 0.218-2.954), marital status (p-v=0.799, OR=1.296, 0.477-3.524), employment status (p-v=0.075, OR=0.345, 0.122-0.974), and the incidence of HIV and AIDS at the Harapan Health Center.